Harnessing technology to enhance oral health literacy among Afghan women: an interprofessional community-engaged initiative - Farokhi, Moshtagh R.; Muck, Andrew E.; Nathan, Hamsini; Yan, James; Estacio, Alvin; Su, Ruoxuan; Stone, Melanie; Mandlik, Nandini; Worabo, Heidi (Frontiers in Public Health, 2025)
IntroductionOngoing socio-political instability has resulted in a growing influx of Afghan women with limited literacy skills resettling in the United States (U.S.). These women face considerable barriers in accessing oral and general healthcare services, exacerbated by limited literacy. This study aimed to explore Afghan women’s challenges in accessing healthcare services and develop a technology-enabled intervention to enhance their health.MethodsAn interprofessional (IP) team of researchers collaborated with community advocates and leaders to gather participants’ insights about preventive health. Participants identified WhatsApp as their preferred platform for receiving health information. Trained interpreters were employed to bridge cultural and linguistic gaps. The first phase involved conducting pre-intervention surveys to assess participants’ experiences with the availability, accessibility, and affordability of healthcare services. Culturally tailored oral health messages were developed using the interactive Canva platform. These videos incorporated messages in English, Pashto, and Farsi that were shared through WhatsApp, to accommodate varying literacy levels. The second phase emphasized hands-on demonstrations to illustrate oral hygiene techniques, and a customized rubric was used to assess participants’ competency. Pre- and post-surveys for the pilot study assessed changes in knowledge and behavior, which helped refine the intervention protocol. Follow-up interviews were conducted six months post-intervention, assessing variations in outcome.ResultsForty-three Afghan women aged 19 to 57 participated in the study. Demographic data revealed that 58% identified Pashto as their primary language, 46% had received little to no formal education, and 77% were homemakers. Key barriers to healthcare access included financial constraints (91%), limited English proficiency (70%), low literacy levels (63%), and transportation challenges (56.3%). Post-intervention data revealed statistically significant improvements in participants’ oral hygiene and dietary knowledge (p < 0.05). Assessment of brushing and flossing techniques indicated increased performance scores from pre-to post-intervention (p < 0.001). At the six-month post-intervention follow-up, 20 women participated. 80% (n = 16) reported reduced consumption of sugary beverages, while 95% (n = 19) indicated improved oral hygiene practices.ConclusionThis study supports the effectiveness of a culturally responsive, technology-facilitated oral health intervention in enhancing self-care behaviors among Afghan refugee women. The findings suggest that healthcare providers should adopt patient-centered, community-engaged approaches to advance health outcomes. Technology-based interventions can effectively address constraints in health literacy.